Implementation of the Concept of "Bring Your Own Device" (BYOD) within the Scope of Labour Law - Hasan Alparslan Ayan (Annales de la Faculté de Droit d’Istanbul)
The process of digitalisation has a profound impact on the global landscape. The ramifications of this phenomenon on the workforce are inescapable. Technological developments exert an influence on employment relationships. From this point forward, information technology (IT) devices will become a requisite component for employees in order to fulfil the obligations inhe-rent to an employment contract. It is therefore becoming more common for employees to use the devices they bring to the workplace. The concept of BYOD (Bring Your Own Device) refers to the use of an employee’s personal IT devices for work-related purposes. Concurrently, this situa-tion leads to issues within the employment relationship. To resolve these issues, it is essential to consider the BYOD concept within the context of labour law. The aim of this study is to evaluate the characteristics of the BYOD concept in employment relationships in comparison with German and Turkish labour law. In consideration of the nature of BYOD, only situations of the utilisation of IT devices will be addressed, and the use of other work resources will not be subject to evaluation. Although there is no direct court decision on the BYOD, the decisions of the Turkish Constitutional Court and the Court of Cassation, as well as the German Federal Labour Court and the Court of Justice of the European Union, which pertain to this concept, will be included in this study. As the primary focus of this article is on the BYOD concept, a concise overview of alternative concepts is provided. After this juncture, the employer’s right of the management and workplace practises will be analysed within the context of BYOD. In the context of the use of personal IT devices within the framework of the employment relationship, certain issues emerge that affect the work and rest periods of employees. In addition, the BYOD application is inextricably lin-ked to the issue of personal data. It is an inevitable consequence of the BYOD that an emplo-yee’s personal data, in conjunction with third parties, will be on the IT devices. Therefore, mea-sures have been developed to protect personal data on IT devices. These topics will be explai-ned under mobile device management (MDM) tools. The final issue to be addressed is the legal status of software on the employee’s IT devices. In this context, the issues of intellectual pro-perty rights and licencing agreements will also be discussed in a separate section dedicated to the BYOD.